Project on Human Development in Chicago Neighborhoods (PHDCN): My Child's Exposure to Violence, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the My Child's Exposure to Violence instrument. This detailed primary caregiver report instrument was administered to Cohorts 0, 3, 6, and 9 and obtained information regarding the subject's lifetime and past-year exposure to violent events. The primary caregiver report instrument is closely related to PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): MY CHILD'S EXPOSURE TO VIOLENCE, WAVE 2, 1997-2000 (ICPSR 13619) and is complemented by the subject-report instrument, PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): MY EXPOSURE TO VIOLENCE (SUBJECT AND YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13697).